2022
DOI: 10.3390/polym14020279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Cellular Effects of Polyethylene Glycol (PEG) Derivatives

Abstract: Nowadays, polyethylene glycols referred to as PEGs are widely used in cosmetics, consumer care products, and the pharmaceutical industry. Their advantageous properties such as chemical stability, low immunogenicity, and high tolerability explain why PEGs are applied in many fields of pharmaceutical formulations including parenteral, topical, ophthalmic, oral, and rectal preparations and also in modern drug delivery systems. Given their extensive use, they are considered a well-known group of chemicals. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…These findings agree with previous literature, [9][10][11][12] which has shown that colorectal adenocarcinoma (Caco-2) cells exposed to 4000, 6000, and 10 000 Da PEG lead to a viability above 90% if the PEG concentration was between 0.01% and 4% w/v, while 400 and 15 000 Da PEG was toxic (viability <50%) at a concentration of 4% w/v. [11] In HeLa cells, 400, 1000, 2000, and 4000 Da PEG at low concentrations (≤0.5% w/v) lead to a cell viability close to 100% and viability of >90% at higher concentrations (≥1% w/v).…”
Section: Impact Of Peg Treatment On Cell Behavior and Viabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…These findings agree with previous literature, [9][10][11][12] which has shown that colorectal adenocarcinoma (Caco-2) cells exposed to 4000, 6000, and 10 000 Da PEG lead to a viability above 90% if the PEG concentration was between 0.01% and 4% w/v, while 400 and 15 000 Da PEG was toxic (viability <50%) at a concentration of 4% w/v. [11] In HeLa cells, 400, 1000, 2000, and 4000 Da PEG at low concentrations (≤0.5% w/v) lead to a cell viability close to 100% and viability of >90% at higher concentrations (≥1% w/v).…”
Section: Impact Of Peg Treatment On Cell Behavior and Viabilitysupporting
confidence: 93%
“…[6] During this intracellular redistribution process, PEG has a very high residence time in cells, which can even exceed 96 h. [5] When the concentration of extracellular solutes increases by PEG addition, water is forced out of the cell by osmotic pressure which leads to a decreased cell volume with strong effects on the cells' physiological processes, cytotoxicity, and mechanics. [7,8] PEG is considered to be almost nontoxic in medical applications; [9] however, cytotoxicity of different MWs and concentrations of PEG has been reported in various crowding studies, [9][10][11][12] mainly due to hyperosmotic stress. [9] Metabolically activated low MW PEG (200-400 Da) has also been reported to have genotoxic effects on numerous cell lines.…”
mentioning
confidence: 99%
“…For example, Ha Pham Le Khanh and his collaborators investigated the cellular effects of PEG derivatives. Their results indicated that PEGs with small molecular weight could decrease cell viability significantly [14]. DAVID A. HEROLD's study suggested that acid metabolites of PEGs with small molecular weight are calcium chelators and are associated with hypercalcemia [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is excreted through the kidneys without accumulating in the body and is widely used commercially in different pharmaceutical formulations. 10,11 Furthermore, PEG hydrogels can accelerate wound healing. 12…”
mentioning
confidence: 99%
“…It is excreted through the kidneys without accumulating in the body and is widely used commercially in different pharmaceutical formulations. 10,11 Furthermore, PEG hydrogels can accelerate wound healing. 12 Hyaluronic acid is widely used in esthetic medicine to stimulate soft tissue enlargement and skin rejuvenation owing to its high water content, excellent biocompatibility, and similarity to human tissues.…”
mentioning
confidence: 99%